Combination and sequential evaluation of acute-on-chronic liver failure (ACLF) and hyponatremia and prognosis in cirrhotic patients. Issue 1 (January 2020) - Pereira, Gustavo; Baldin, Caroline; Piedade, Juliana; Reis, Vanessa; Valdeolivas, Tatiana; Victor, Lívia; Guimarães, Lívia; Duarte, Joana; Veiga, Zulane; Alcântara, Camila; Fernandes, Flávia; Pereira, João Luiz
Abstract: Background: Few studies have evaluated whether combination and sequential evaluation of ACLF (acute-on-chronic liver failure) and hyponatremia aids prognosis. Aims: Describe clinical course and determine prognostic capability of assessing ACLF and hyponatremia at specific time-points. Methods: Prospective study with inclusion of 376 patients. ACLF and hyponatremia were evaluated at days 1 and 7 and classified as persistent, transient, de novo or absent. Follow-up was 90 days. Results: At inclusion, ACLF was diagnosed in 99 patients. Reversal was observed in 57 patients and was associated with lower creatinine and ACLF grade. De novo ACLF developed in 19 patients, and MELD (model of end-stage liver disease) score and lower albumin were predictive factors. Hyponatremia was present in 76 patients (persistent, transient and de novo in 27, 24 and 25 respectively). ACLF at D7 had the lowest survival compared to transient or no ACLF (21, 57 and 80%, p < 0.0001). Hyponatremia at admission was associated with low survival (35%) whereas survival was higher for de novo or absent cases (70%), p < 0.001. In multivariate analysis ACLF at D7 and hyponatremia at D1 were predictors of survival. Conclusion: ACLF and hyponatremia are dynamic and evaluation of both conditions at different time-points identifies patients at higher risk of short-term mortality.